Persepsi Mahasiswa Mengenal Lingkungan Belajar Klinik dan Motivasi Belajar Pada Suatu Program Studi Ners - Suryani Suryani; Rossi Sanusi; Tridjoko Hadianto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: Effective learning should be based on an understanding of how students learn. Students who are well adjusted will be actively involved in learning. The role of motivation will encourage individuals to have appropriate strategies to guide their learning, to depthly process the information which in turn produces better learning achievement. Environment creates a learning atmosphere that influences students learning motivation. This study was aimed to find out the correlation between students’ perception of clinical learning environment and learning motivation. Method: The study used quantitative method with cross sectional approach. 70 Ners students of Aisyiyah University of Yogyakarta academic year 2015/2016 answered the Clinical Learning Environment and Supervision (CLES) and Motivated Strategies for Learning Questionnaire (MSLQ) questionaires. Pearson test was used to analyze the data.Results: Most of the students (77.1%) showed positive perception about the clinical learning environment. They were more likely to be motivated extrinsically than intrinsically.The highest value of task value motivation subscales shows a mean value of 5.79 (SD = + 0.67) while the lowest value in the anxiety test sub-scale shows a mean of 3.52 (SD = + 1.23). The clinical learning environment of the head of the room leadership style sub-scale has a weak positive correlation with the motivation to learn (r = 0.297 and p = 0.012).Conclusion: There is a weak positive correlation between students’ perception of clinical learning environment and learning motivation. Clinical learning environment needs to be well prepared to meet the needs and improve students learning motivation.